2019
DOI: 10.31234/osf.io/54pnh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inconsistent lateralisation of language functions: a risk factor for language impairment?

Abstract: Journal section: Cognitive Neuroscience Number of pages (incl. references and figures/tables): 48 Number of words in the whole manuscript (incl. references): 8812 Number of words in the abstract: 249 Number of figures: 7 Number of tables: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…We also note that regional lateralization tends to change across tasks in both HC and LTLE. This is in line with previous findings suggesting that hemispheric lateralization for language is not a rigid and a unitary construct ( Bradshaw et al, 2017 , 2019 ) but varies according to regions and specific processes. Similarly, it was shown that different memory processes and types of stimuli could result in different memory lateralization ( Golby et al, 2002 ; Milian et al, 2015 ; Andreau and Torres Batán, 2019 ; Palacio and Cardenas, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…We also note that regional lateralization tends to change across tasks in both HC and LTLE. This is in line with previous findings suggesting that hemispheric lateralization for language is not a rigid and a unitary construct ( Bradshaw et al, 2017 , 2019 ) but varies according to regions and specific processes. Similarly, it was shown that different memory processes and types of stimuli could result in different memory lateralization ( Golby et al, 2002 ; Milian et al, 2015 ; Andreau and Torres Batán, 2019 ; Palacio and Cardenas, 2019 ).…”
Section: Discussionsupporting
confidence: 93%